Home buyers requirements for housing development within districts in Selangor - Yong, Hong Lee (2006)
Despite its resilience, the residential property sector is getting increasingly competitive and the developers are looking at the slower take-up rates and flattish earnings performance. Property developers have to confront challenges in maintaining market share and profit margin. Many developers have to relaunch the sales of the houses due to the poor sales of the houses. The developers have to keep themselves updated with the current market situation and hence, to develop the strategy that can enable them to boost the sales of the houses. Therefore, this study has been developed with the aim to identify the popular types of houses that are preferred by the buyers, the basic quality and features of the house preferred by different ethnic groups and to identify the various strategies adopted by developers to market the residential houses. The study was conducted through interviews, which was carried out extensively with the successful developers, and also through questionnaires. The data were analyzed using relative index and other non-parametric statistical technique. It was found that the most popular type of house preferred by the buyers is double storey link house. Each ethnic group of buyers has their own preference of the basic quality and features which encourage them to purchase the house. The strategies that the developers have to undertake in order to market their houses are the pricing, using more channels to advertise their products and to provide higher loan margin facilities to the potential buyers.